2012
DOI: 10.5498/wjp.v2.i2.33
|View full text |Cite
|
Sign up to set email alerts
|

Risks of suicidality in adult patients with epilepsy

Abstract: This is the first study which systematically estimated the prevalence and risks of suicidality in a homogenous group of patients with epilepsy. This study emphasizes the importance of epilepsy itself as a risk for suicidality and not its treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 32 publications
3
16
0
3
Order By: Relevance
“…In this study, the prevalence of lifetime suicidal ideation and attempt among people living with epilepsy and their possible associations with different variables were assessed. The prevalence of suicidal ideation was 29.8% which is higher than the result reported in Egypt (23.5%) [ 12 ], in Washington tertiary epilepsy clinics (11.9%) [ 21 ]. These might be due to the difference in sample size, study design, study participants, culture, time variation, and settings.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In this study, the prevalence of lifetime suicidal ideation and attempt among people living with epilepsy and their possible associations with different variables were assessed. The prevalence of suicidal ideation was 29.8% which is higher than the result reported in Egypt (23.5%) [ 12 ], in Washington tertiary epilepsy clinics (11.9%) [ 21 ]. These might be due to the difference in sample size, study design, study participants, culture, time variation, and settings.…”
Section: Discussionmentioning
confidence: 70%
“…Different studies indicated that people with epilepsy are at higher risk for suicidal thoughts and attempts [ 9 , 10 ] with an estimated lifetime prevalence rate ranged from 3.3 to 14.3% [ 11 ] or even up to 35% [ 12 ]. This rate has been reported to be 6–25 times higher with temporal lobe epilepsy (TLE) compared to 1.4–6.9% in general population [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…U pacjentów z myślami samobójczymi obserwuje się też zaburzenia wydzielania neurotransmiterów, np. obniżenie stężenia serotoniny, noradrenaliny [17,18]. Według Fazel i wsp.…”
Section: Zaburzenia Depresyjne Rozpowszechnienieunclassified
“…Hamed i wsp. [18] przeprowadzili badania na 200 dorosłych chorych na padaczkę, w których oszacowali ryzyko i rozpowszechnienie samobójstw, uzyskując wynik na poziomie 35%. Tutaj także najczęstszymi zaburzeniami psychicznymi były kolejno: depresja i lęk.…”
Section: Zaburzenia Depresyjne Rozpowszechnienieunclassified
“…Риск развития суицидального поведения у больных эпилепсией повышают социальные, экономические и психологические трудности, такие как низкий социоэкономический статус, проблемы с достижением академических и профессиональных успехов, жилищные сложности, ощущение потери локус-контроля, невозможность получения водительских прав, а также другие связанные с внешней стигмой ограничения [35][36][37]. К психологическим факторам, увеличивающим риск возникновения суицидальных мыслей и попыток у больных, относят опыт межличностного насилия и использование неадаптивных копинг-стратегий, таких как бегство-избегание [12,32,38].…”
unclassified